Personal charisma or the economy?: Macroeconomic indicators of presidential approval ratings in Brazil - Alex Luiz Ferreira; Sérgio Naruhiko Sakurai (EconomiA, 2013)
We test the degree to which presidential approval ratings are related to a series of economic indicators, controlling for the political scenario in Brazil. Results, from 1999M9 until 2010M5, show that unemployment and the minimum wage are the main variables that affect the ratings. There is also evidence that President Luis Inácio Lula da Silva has a higher approval rate than President Fernando Henrique Cardoso, keeping constant a reasonable number of important domestic and foreign indicators. However, when controlled for a time trend, differences in popularity between both presidents vanish as the sample size grows. Our results support the conclusion that the good state of the economy (given no political turmoil) is the main factor that explains and predicts Lula's high popularity. – – O artigo testa em que medida as taxas de aprovaç\~ao do presidente do Brasil est\~ao relacionadas com uma série de indicadores econômicos, controlando para o cenário político. Os resultados, de 1999M9 até 2010M5, mostram que o desemprego e o salário mínimo s\~ao as principais variveis econômicas que afetam a aprovaç\~ao. Também existe evidência que o Presidente Luis Inácio Lula da Silva tem uma maior taxa de aprovaç\~ao que o Presidente Fernando Henrique Cardoso, mantendo constante um número razoável de importantes indicadores domésticos e estrangeiros. No entanto, quando se controla para uma tendência determinista, as diferenças de popularidade entre os dois presidentes desaparecem com o aumento da amostra. Os resultados permitem concluir que o bom estado da economia (supondo a ausência de choques políticos) é um dos principais fatores que explica e prediz a alta popularidade do Presidente Lula.
Keywords: H11; H77; H83; E02; C52; 330; Brazilian President; Approval ratings; Macroeconomy